2018
DOI: 10.1016/j.toxrep.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxicity of Euphorbia triaculeata Forssk. extract on mice bone marrow cells in vivo

Abstract: HighlightsThe study deals with the effect of E. triaculeata extract against the genotoxicity of the standard drug cyclophosphamide (CP) treatment in mice.E. triaculeata extract did not show significant changes on mitotic indices or in induction of chromosomal aberrations in mice bone marrow cells.E. triaculeata extract at the three doses used did not increase the number of micronucleated polychromatic erythrocytes.Pretreatment with E. tuberculata extract significantly reduced the clastogenicity of CP.The intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Other botanical extracts have been evaluated for mutagenicity. Mutagenic studies on extracts from the plant Euphorbia triaculeata showed that it is not mutagenic and provides protection from the mutagenic effects of cyclophosphamide [31]. A study on a novel taste modulating powder derived from Cordyceps sinensis showed this product was not mutagenic in the Ames test and these results were supported in the micronucleus assay [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other botanical extracts have been evaluated for mutagenicity. Mutagenic studies on extracts from the plant Euphorbia triaculeata showed that it is not mutagenic and provides protection from the mutagenic effects of cyclophosphamide [31]. A study on a novel taste modulating powder derived from Cordyceps sinensis showed this product was not mutagenic in the Ames test and these results were supported in the micronucleus assay [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some in vivo studies also corroborate the anticancer potential and safety of Euphorbia extracts and compounds. For example, the methanolic extract of E. triaculeata Forssk., when tested in albino mice at 250 to 1000mg/kg body weight, is not genotoxic or clastogenic, while the pre-treatment with this extract inhibits the clastogenicity induced by cyclophosphamide without impairing its cytotoxic potential [117].…”
Section: Other Biological Activity Of Euphorbia Plantsmentioning
confidence: 99%
“…It was reported earlier that several anti-tumour compounds act through the anti-mutagenic mechanism. Hence searching for the antimutagenic compounds represents a rapidly expanding field of cancer research plants having antimutagenic potential can also be used as an adjuvant with the chemotherapeutic drugs to reduce the side effects associated with the chemotherapy (16).…”
Section: Discussionmentioning
confidence: 99%